Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1103/physrevc.83.041301
|View full text |Cite
|
Sign up to set email alerts
|

Perturbative interpretation of relativistic symmetries in nuclei

Abstract: Perturbation theory is used systematically to investigate the symmetries of the Dirac Hamiltonian and their breaking in atomic nuclei. Using the perturbation corrections to the single-particle energies and wave functions, the link between the single-particle states in realistic nuclei and their counterparts in the symmetry limits is discussed. It is shown that the limit of S-V=const and relativistic harmonic oscillator (RHO) potentials can be connected to the actual Dirac Hamiltonian by the perturbation method… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
113
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(122 citation statements)
references
References 31 publications
(42 reference statements)
9
113
0
Order By: Relevance
“…In this case, one cannot have exact spin symmetry (i.e., V = S) since now − = −(V − S) acts as binding potential. This behavior has been related by several authors to the perturbative nature of spin and pseudospin symmetry, namely that in the case of fermions (antifermions) the pseudospin (spin) symmetry is nonperturbative for nuclear mean-field potentials [6,[8][9][10]. Note, however, that for harmonic oscillator systems one can have exact pseudospin and spin symmetries for fermions and antifermions respectively [11].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In this case, one cannot have exact spin symmetry (i.e., V = S) since now − = −(V − S) acts as binding potential. This behavior has been related by several authors to the perturbative nature of spin and pseudospin symmetry, namely that in the case of fermions (antifermions) the pseudospin (spin) symmetry is nonperturbative for nuclear mean-field potentials [6,[8][9][10]. Note, however, that for harmonic oscillator systems one can have exact pseudospin and spin symmetries for fermions and antifermions respectively [11].…”
Section: Introductionmentioning
confidence: 95%
“…In previous works in which the perturbative nature of pseudospin (or spin in the case of antifermions) was related to the onset of the respective symmetry, one would either examine the effect the pseudospin-orbit or spin-orbit term on the energy splittings of the respective doublets [6,8,9] or analyze the convergence of a perturbation expansion in the respective potential strength [10]. In Ref.…”
Section: Spin and Pseudospin Symmetries In The Dirac Hamiltonianmentioning
confidence: 99%
“…More reviews on the PSS can be found in the literature [16] and the references therein. Recently, a perturbation method was adopted to investigate the spin and pseudospin symmetries by dividing the Dirac Hamiltonian into the part of possessing the exact (pseudo)spin symmetry and that of breaking the symmetry [17].Despite the large number of studies on PSS, it is still not fully understood the origin of PSS and its breaking mechanism since there is no bound states in the PSS limit. Hence, many efforts are devoted to compare the contributions of different terms in the Schrödinger-like equation for the lower component of Dirac spinor to the pseudospin energy splitting.…”
mentioning
confidence: 99%
“…More reviews on the PSS can be found in the literature [16] and the references therein. Recently, a perturbation method was adopted to investigate the spin and pseudospin symmetries by dividing the Dirac Hamiltonian into the part of possessing the exact (pseudo)spin symmetry and that of breaking the symmetry [17].…”
mentioning
confidence: 99%
“…[25,26]. In addition, it was noted that, unlike the spin symmetry, the pseudospin breaking cannot be treated as a perturbation of the pseudospin-symmetric Hamiltonian [27]. The nonperturbation nature of PSS has also been mentioned in Ref.…”
Section: Introductionmentioning
confidence: 99%